Experimental two-factor response surface optimisation of methane yield from pig manure co-digested with banana peel, cabbage and pumpkin waste - Ogunniyi, Olalekan Joseph; Mbohwa, Charles; Onu, Peter; Chikumba, Steadyman; Phuluwa, Humbulani Simon (Edelweiss Applied Science and Technology, 2026)
This study optimised methane yield from pig manure (PM) co-digested with banana peel, cabbage and pumpkin residues (BCP). A two-factor response surface methodology was used, with PM fraction and batch digestion time as factors. Blank-corrected biochemical methane potential (BMP) was the main response, with methane volume and energy yield as supporting responses. Design-Expert was used for quadratic modelling, while Python supported model checking and sensitivity analysis. BMP ranged from 191.48 to 468.23 N mL CH₄ g⁻¹ VS. The PM fraction contributed 98.975% of the model sum of squares, compared with 0.855% for digestion time. The absolute maximum occurred at PM0:BCP100 after 60 days, but this was mono-digestion. The highest tested co-digestion BMP was 332.85 N mL CH₄ g⁻¹ VS at PM50:BCP50 after 60 days. At 45 days, the same blend achieved 324.95 N mL CH₄ g⁻¹ VS, retaining 97.6% of the 60-day yield. Feedstock composition affected methane yield more strongly than digestion time. PM50:BCP50 at 45 days is a time-efficient laboratory-scale condition requiring validation in continuous digesters.